Swiss Direct Democracy and Regulation of Banking Sector - Miroslaw Matyja (Technium Social Sciences Journal, 2020)
The aim of this article is to analyze the influence of the Swiss political system on the country’s banking sector. Is the Swiss direct democracy, which has no counterpart in any other country, an advantageous factor for the development and functioning of the banking sector? In order to fully answer this question, the author has analyzed the results of direct voting on the Swiss bank regulations. He has concluded that there is an important and direct influence of the political system on the functioning of the financial sector. The analysis of the results of various federal referenda confirms the thesis that the Swiss direct democracy (with its instruments of popular initiative and referendum) has a decisive influence on the regulatory process in the country’s banking sector.